Corporate governance : external auditors and their opinions. - Mah, Yew Fai. (2008)
The increasing awareness and emphasis on corporate governance may be traced to the occurrence of many company failures over the past few years. The term corporate governance can be defined as the way corporate entities are governed, and the issues facing the board of directors, such as the interaction with top management, and relationships with the owners and others interested in the affairs of the company, including creditors, debt financiers, analysts, auditors and corporate regulators. Our study was conducted to identify the opinions of external auditors on various issues of corporate governance.